The The Effect of Strategy Training on Vocabulary Learning of EFL University Students - Seffar, Salma (International Journal of Language and Literary Studies, 2020)
This study investigated the effect of training in five vocabulary learning strategies (VLS) on the vocabulary learning of EFL university students. The five vocabulary learning strategies were ‘Dictionary Work’, ‘Word Cards’, ‘Semantic Mapping’, ‘Word Parts’, and ‘Guessing from Context’. Forty-eight first-year university students, in both the control group (24 students receiving English language courses) and the experimental group (24 students receiving English language courses besides VLS training) belonging to similar proficiency and vocabulary size levels, participated in the study. Data were collected utilizing two research instruments namely a vocabulary learning strategy questionnaire, pre-and post-tests of vocabulary learning ability. The vocabulary learning strategy questionnaire was used to elicit what types of vocabulary learning strategies the subjects employed while they learned and memorized the vocabulary taught independently outside and inside the class. The pre-test was employed to determine pre-existing knowledge of the participants. The posttest was administered to identify the impact of vocabulary learning strategy instruction on the students’ vocabulary knowledge. Descriptive statistics and t-test showed that after introducing vocabulary learning strategies training (VLST) in class, subjects from the experimental group used more VLS and significantly outperformed subjects of the control group in their ability to learn new words.